Prediction of early pregnancy failure by use of first trimester ultrasound screening - Kumari, Snigdha; Roychowdhury, Joydeb; Biswas, Supratim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Spontaneous miscarriage is defined as an involuntary termination of pregnancy before 20th week of gestation or spontaneous expulsion of fetus below a fetal weight of 500 gm. The introduction of ultrasound into the obstetrical practice has been extremely useful in providing better understanding of the etiology of the first trimester spontaneous abortion and a basis for its clinical classification and management. The aims and objective of this study is to assess the early pregnancy developmental changes in first trimester ultrasound screening, identify abnormal ultrasound parameters and correlate the ultrasonic findings with the clinical outcomes and also to analyze the success of conservative management on patients. Methods: The study included 150 patients attending OPD/emergency within 5-12 weeks of gestation fulfilling the exclusion and inclusion criteria. Results: The abortion rate in our study was 16%. Seventy two percent of abortion occurred at 8-12 weeks of gestation. Threatened abortion was noted in 10% of the patients. Sixteen percent of patients had abnormal USG findings in terms of large yolk sac, abnormal mean sac diameter, crown rump length, embryonic bradycardia, increased resistive index and intrauterine hematoma. Conclusions: This study emphasizes the role of ultrasound in prediction of early pregnancy failure in first trimester. It also stresses on the importance of learning obstetric ultrasound and performing obstetric practice in the community with precision and perfection.